Analisis Pemahaman, Produk, dan Tingkat Religiusitas terhadap Keputusan Mahasiswa IAIN Menjadi Nasabah Bank Syariah Cabang Salatiga - Anton Bawono; Milatunnikmah Finisia Rahajeng Oktaviani (IAIN Salatiga, 2016)
The purpose of this research is to analyze the understanding, product, and level of religiosity towards students’ decision of being costumer of Islamic bank. This is a quantitative research. The object of this research is students of State Institute for Islamic Studies of Salatiga. The writer took 100 students as sample of this research. The method used to collect the data is questionnaire. The data is analyzed using test of reliability, validity, statistic and classical assumption. The research findings showed that the product of sharia bank has significant and positive influence. It occurred because the product offered by sharia bank is innovative. The variable of understanding about sharia bank and level of religiosity towards students’ decision of being costume of sharia bank has positive influence but insignificant